1985
DOI: 10.1159/000233657
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of Bacterial Antigens in Normal Adult Mice

Abstract: Marked differences were seen in the oral absorption of Boivin antigen (BA) and flagellin (FLA) using antigens labelled by 3H-dinitrophenylation. Thus, after feeding 3H-DNP-FLA, a large proportion of the label was rapidly absorbed, concentrated and degraded by the liver so that no antigenic material could be recovered from the circulation. In contrast, the absorption of 3H-DNP-BA was low and slow; the absorbed material appeared stable and not readily taken up by the liver, so that 8–20% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Presumably, FLA would be quickly de graded in the intestinal tract and rapidly absorbed in to the liver, while BA, being more stable, is expected to be absorbed more slowly, mostly in macromolecu lar form, and significant amounts of it should be re coverable from the circulation. These expectations were indeed borne out as seen in later studies [6].…”
Section: Discussionsupporting
confidence: 61%
“…Presumably, FLA would be quickly de graded in the intestinal tract and rapidly absorbed in to the liver, while BA, being more stable, is expected to be absorbed more slowly, mostly in macromolecu lar form, and significant amounts of it should be re coverable from the circulation. These expectations were indeed borne out as seen in later studies [6].…”
Section: Discussionsupporting
confidence: 61%
“…Second, uptake studies indicated a better uptake of antigenically intact ovalbumin than Limulus-reactive LPS over the intestinal epithelium. For intact macromolecules such as proteins (of food or bacterial origin), the fraction taken up antigenically intact has been calculated to be around 10-3 to 10-4 of the amount given intragastrically (22,35). There is no indication that bacterial macromolecules per se are more efficiently taken up than, e.g., dietary proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Mice challenged with large doses of LPS enterally did not develop diarrhea, but there were scattered foci of vascular damage in the areas of the gut presumably exposed to the highest concentration of LPS. The absorption of LPS from the mouse intestine is slow and in small amounts (32), which may explain the localized vascular lesion and the absence of significant fluid exudation with enteral challenge. There are several possible mechanisms by which LPS could play a role in clinical acute diarrhea.…”
Section: Discussionmentioning
confidence: 99%